2022
DOI: 10.3389/fnagi.2022.967747
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota may be involved in Alzheimer’s disease pathology by dysregulating pyrimidine metabolism in APP/PS1 mice

Abstract: IntroductionAlzheimer’s disease (AD) is the most common form of dementia worldwide. The biological mechanisms underlying the pathogenesis of AD aren’t completely clear. Studies have shown that the gut microbiota could be associated with AD pathogenesis; however, the pathways involved still need to be investigated.AimsTo explore the possible pathways of the involvement of gut microbiota in AD pathogenesis through metabolites and to identify new AD biomarkers.MethodsSeven-month-old APP/PS1 mice were used as AD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…APP/PS1 mice combining 16SrRNA gene sequencing and extensively targeted metabolomics revealed that B. firmus , Rikenella , Clostridium sp. culture-27 , and deoxyuridine might be important biomarkers of AD ( Feng et al, 2022 ). Based on the GM differences in feces and blood established in the preliminary study, Li et al built a random forest model based on 11 genera of differences in stools and blood from AD patients and NC.…”
Section: Microbiome-based Ad Biomarkersmentioning
confidence: 99%
“…APP/PS1 mice combining 16SrRNA gene sequencing and extensively targeted metabolomics revealed that B. firmus , Rikenella , Clostridium sp. culture-27 , and deoxyuridine might be important biomarkers of AD ( Feng et al, 2022 ). Based on the GM differences in feces and blood established in the preliminary study, Li et al built a random forest model based on 11 genera of differences in stools and blood from AD patients and NC.…”
Section: Microbiome-based Ad Biomarkersmentioning
confidence: 99%
“…According to the model predictions and brain metabolome data, the microbiome may play a key role in nucleotide salvage in the brain, which is essential for DNA damage repair and cellular homeostasis 88 . In addition, an association between neurodegeneration and microbial pyrimidine metabolism was observed in an experimental mouse model of Alzheimer’s disease 89 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the model predictions and brain metabolome data, the microbiome may play a key role in nucleotide salvage in the brain, which is essential for DNA damage repair and cellular homeostasis 88 . In addition, an association between neurodegeneration and microbial pyrimidine metabolism was observed in an experimental mouse model of Alzheimer's disease 89 . In summary, we comprehensively characterized microbiome-host interactions in mice and identified pronounced aging-associated changes in these interactions primarily driven by a loss of microbial metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Among them, the metabolic pathway involved in the gut microbiota is an important way to affect the host. 14 For example, short-chain fatty acids (SCFAs) are the main metabolites produced by gut microbiota through the metabolism of indigestible dietary fibers. 15 SCFAs have been shown to participate in the pathological process of AD in various ways.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have explored the relationship between gut microbiota and metabolic pathways in APP/PS1 mice through 16S rRNA gene sequencing and metabolomics. 14 , 18 However, most current studies only focus on the alteration and correlation of metabolite abundance in feces and blood, while there is a lack of research on the correlation characteristics of the spatial distribution of metabolites, gene expression levels, and pathological changes in the brains of AD. In this study, we not only used 16S rRNA gene sequencing and metabolomics to explore the variation characteristics of gut microbiota abundance and serum metabolism abundance but also combined spatial metabolomics, transcriptomics, neuroimaging, and pathology to explore the changes in the brain and identify their correlation in APP/PS1 mice.…”
Section: Introductionmentioning
confidence: 99%